Application of Evaporative Cooling System for Post Harvest Handling of Agricultural Products - Armansyah H. Tambunan; Hedi R. Rismawan; Isabella Silalahi (Jurnal Keteknikan Pertanian, 1999)
Post harvest handling and treatment of agricultural prodz~ct isextremely important in maintaining all of the possible qzralify of the prodzilrct. Most of the product needs to be handled and treated at low temperature. Duly. a cheap and easy-to-handle cooling facility is very important to be provitied nearer to producer's/ farmer's location. The objectives of the experiment were to design and evaluate the performance of an evaporative cooling system, uwd to develop a simulation model for predicting the performance and temperature distribution inside the storage room. Experimental data showed that the performance of the design was fairly good and acceptable. The cooling system could keep the temperature of product under ambient temperature, although the optimal temperaturecouldn't be reached. Performance of the design could be increased by improving the performance of nozzle, fan and the insulation system of the storage wall.